Kearifan Lokal Aktivitas Masyarakat Hindu Bali sebagai Sumber Belajar Pendidikan Pancasila dan Kewarganegaraan - Alhudawi, Usman; Malihah, Elly (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2020)
This study aimed to examine the potential of local wisdom in the activities of the Balinese Hindu community in Serdang Bedagai Regency as a learning resource for Pancasila and Citizenship Education (PPKn). Researchers used a qualitative approach to ethnographic research methods. This research was conducted in Pegajahan Village, Pegajahan District, Serdang Bedagai Regency, North Sumatra. The results showed that the value of local wisdom in the activities of the Balinese Hindu community in Pegajahan Village could be contained in learning and strengthened the cultivation of various characters in PPKn learning. The integration of local wisdom values from the activities of the Balinese Hindu community in Pegajahan Village in the PPKn learning activities had the potential to succeed, however, there was an obstacle in its implementation.